Tumor Necrosis Factor Alpha p55 Receptor Is Important for Development of Memory Responses to Blood-Stage Malaria Infection - Li, Ching (American Society for Microbiology, 2000)
Tumor necrosis factor alpha (TNF-α) is associated with malarial pathology in both humans and mice. In Plasmodium chabaudi chabaudi (AS) infections, the production of TNF-α and reactive metabolites from macrophages are also thought to play a role in controlling acute parasitemia. Since many of the biological functions of TNF-α are effected through the p55 receptor (p55R), mice made defective in this receptor via a targeted gene disruption (p55R(−/−)) have been used to study its involvement in the immune response against P. chabaudi chabaudi and in the pathology associated with this infection. In the absence of the p55R, mice could overcome their primary infection, although higher acute-blood-stage parasitemias and more significant recrudescences were observed. Hypoglycemia, hypothermia, loss of erythrocytes, and loss of body weight, which occur transiently in this infection, were exacerbated by the lack of the p55R, but the differences were small, suggesting that other factors affect these symptoms. In contrast to wild-type (WT) mice, a second challenge infection in p55R(−/−) mice resulted in a course of infection similar to a primary infection. The malaria-specific immunoglobulin G antibody response of p55R(−/−) mice was lower than that of WT mice and was not increased by the second challenge infection. These data suggest that p55R(−/−) mice do not develop an efficient memory B-cell response against malarial infection and that this antibody response is important in immunity to reinfection.